Ophiolit zone of Thai Nguyen - Cao Bang - Chương, Văn Đức; Thắng, Trần Văn; Tùng, Văn Đức; Linh, Phan Doãn; Việt, Lê Triều (Vietnam Journal of Earth Sciences, 2018)
Ophiolit zone of Thai Nguyen - Cao Bang started from the border of Vietnam with China, then stretched in passing Cao Bang - Dong Khe - SacCan - to Thai Nguyen. The structure of the ophiolit zone devided into five complex :- Dunite - serpentinit - peridotite complex,- Folliation gabros complex,- Gabros - diabaz complex, ·- Bazan toleit complex,- Sediment of marginal complex.The formation of Ophiolit zone occurred in the beginingPermi and ending in the late of Triassis by overslip of Eurasian plate over Song Hien marginal sea.